ANALISIS PERUMUSAN STRATEGI PENGEMBANGAN BISNIS PADA USAHA FASHION - Aliifa, Aaqilah Meutia; Sumiati, Sumiati (Jurnal Kewirausahaan dan Inovasi, 2022)
Business competition in fashion industry nowadays is increasing along the positive development of this industry in Indonesia. This is also followed by the rapid growth of MSME, particularly in Malang city. The fierce competition between business owners implies the importance of business strategy development in order to help the enterprises compete in the market. Asaff Hijab is a business in fashion industry in Malang city; and hijab is their commodity. Until today, the sales of this company remain unstable, and even tend to decrease. Insufficient human resource and ineffective product marketing have placed the venture in a stagnant position with very few sales. Based on the condition above, the objective of this research is to analyze the company’s internal and external factors to produce the appropriate strategy to develop their business. The primary data was harvested from interviews, while the secondary one was gathered from literatures and documents. The instruments of analysis are IFE Matrix, IFE Matrix, SWOT Matrix, IE Matrix, ad QSPM Matrix. Based on the results of the analysis, the appropriate strategy for Asaff Hijab is market penetration.